Government development assistant programmes and the food and beverage manufacturing sector : awareness, utilisation and perception. - Chong, Mellisa Pei Ling. (2008)
It is one of our goals in this study to analyse the current SME situation in Singapore and to investigate the gap between SMEs and Government Development Assistant Programmes (GDAPs). This study analyses the gap in three parts: awareness, utilisation and perception. The study is conducted via the food and beverage manufacturing industry using the questionnaire as a survey instrument.